Price as a Signal of Product Counterfeiting. The Moderating Role of the Buyer’s Regulatory Focus - Wanat , Tomasz (Studia Oeconomica Posnaniensia, 2018)
When consumers buy second-hand products, for example on e-commerce platforms as eBay or olx, they can quite easily encounter counterfeit products. First of all, buyers should be aware of this menace, moreover they should be able to distinguish a legitimate product from a counterfeit one. Price level can be used as an indicator of product counterfeiting because such products are sold as a small part of the value of legitimate products. The aim of the paper is to assess the buyer’s willingness to use prices as a signal of product counterfeiting. In one experimental study on 117 subjects, it was shown that the price is used as a signal of product quality, however, is not used as a signal of product counterfeiting. Subjects in prevention regulatory focus (higher risk-averse group) do not show greater aversion to low-price products than the subject in a promotion focus state (lower riskaverse group).